ผลของจำนวนแถบสีของตารางทดสอบสีต่อโพรไฟล์สีของระบบการพิมพ์อิงก์เจ็ทแบบถ่ายโอนความร้อนลงบนผ้า - อาทิตยา โง่นทา (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Recently heat transfer inkjet printer is widely used in the textile industry to add hue and pattern for fabrics. One of the problems is the colors printed on the fabric do not match the requirement, to solve this problem is difficult because heat transfer inkjet printing is indirect printing. Thus, this study is interesting in using a color management system (CMS) to solve the problem by comparing the color profiles generated from color test chart with a different number of colors, in order to analyze color of sample images printed by different profile that have the color that match the most requirement. The experiment was done by printing out color test charts with 320, 612, and 1400 colors. Next, printed test chart was heat pressed on two fabrics, that were polyester and TC fabrics. Then the color patches were measured and create color profiles by CMS software. Then a test sheet from each color profile was printed out and evaluated the print quality. From the comparison, the test sheet from color profiles with 1400 colors has the best color saturation and tone reproduction in both polyester and TC fabrics.